In-situ detection sensor for sweat on body surface based on composite nanofibers and preparation method thereof
By using composite nanofibers and liquid metal alloys with gradient wettable structures in the body surface sweat detection sensor, the stability problems of sweat collection and signal transmission are solved, and efficient and accurate sweat detection and signal transmission are achieved.
Patent Information
- Application Number
- CN202510058796.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Existing wearable surface sweat detection sensors are difficult to achieve long-term sustainable monitoring, poor breathability causes inflammation, poor dynamic characteristics, and difficult to adapt to soft and large-deformed skin, resulting in unstable detection signal transmission, and it is difficult to achieve unidirectional penetration and collection of sweat, resulting in cross-contamination of new and old sweat.
The body surface sweat in-situ detection sensor is used based on composite nanofibers. By preparing composite nanofibers with gradient wetting structures, the capillary siphon effect is used to achieve unidirectional transmission of sweat, prevent cross-contamination of new and old sweat, and liquid metal alloy is used as signal transmission electrodes to ensure the stability of signal transmission during deformation.
The one-way controllable collection and diversion of sweat is achieved, which avoids cross-contamination of new and old sweat, ensures the accuracy of detection and the stability of signal transmission. The overall sensor is a porous fiber structure, with good flexibility and breathability, and avoids inflammation caused by long-term wearing.
Smart Images

Figure CN119498836B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of flexible sensing technology, and specifically relates to a flexible electrochemical sensor for detecting physiological information of body surface sweat, in particular to a body surface sweat in-situ detection sensor based on composite nanofibers and a preparation method thereof. Background Art
[0002] Human sweat is rich in electrolytes (Na + , K + , Cl + Physiological markers such as glucose, lactate, urea, etc.), metabolic molecules (glucose, lactate, urea, etc.) and hormones (cortisol, estrogen, etc.) can be used for real-time monitoring of human health information and preventive health interventions. For example, cystic fibrosis can be diagnosed by detecting Cl in sweat. - 、Na + The content of sweat can be used for diagnosis; uric acid in sweat can reflect the intake of purine and can be used to prevent gout. Compared with traditional body fluid detection technologies such as blood, urine and saliva, the sweat detection process does not cause any discomfort or pain, and has the advantages of convenient collection, non-invasive, continuous and real-time. For example, a large number of clinical studies have shown that sweat glucose can replace blood sugar as a daily monitoring indicator for diabetic patients, and is expected to replace invasive blood sugar detection technology, thereby improving the medical experience and further promoting the development of personalized medicine.
[0003] Sweat detection involves sweat extraction, collection and signal sensing, of which sweat extraction and collection are the basis for accurate and reliable detection. However, human sweat secretion is small in volume, volatile, and easily contaminated. An average adult sweats 500-700 ml per day, and the sweat secretion rate per unit skin area is only about 1.0 uL / (min.cm 2 ), even after thermal stimulation, the secretion rate is only about 4.0 uL / (min.cm 2 ); In addition, new and old sweat easily mix together, causing sweat contamination. Traditional sweat detection technologies (such as full-body showers and absorbent hanging bags / patches, etc.) have a complex sweat collection process, require professional equipment and operators, and the collection and detection are carried out separately, with poor real-time performance.
[0004] In recent years, with the rapid development of flexible electronic technology, wearable sweat detection sensors have made a series of breakthroughs. Wearable sweat detection sensors can conformally contact the skin. In 2016, John A. Rogers first proposed a wearable microfluidic chip for sweat detection. Under the combined action of microchannel capillary force and sweat osmotic pressure, sweat can be continuously and controllably collected and discharged, avoiding cross contamination caused by new and old sweat [Science Translatinal Medicine, 2016, 8(366): 366ra165]. Although the use of flexible film substrates (hydrogel, PDMS, etc.) can ensure wearing comfort, the overall air permeability of the film substrate is poor, and long-term wearing can easily cause skin inflammation. Invention patent CN111759359A discloses a multi-channel fiber-based sweat collection and sensing system, which uses a porous fiber structure of fabric to collect sweat, but sweat cannot play a unidirectional permeation function. Although the invention patent application with publication number CN114680883A realizes unidirectional permeation of sweat through multi-layer fiber membrane, it does not solve the problem of flexibility of sweat sensing electrode, and further studies are needed on the stability of signal transmission for in-situ detection of sweat on the body surface. Dae-Hyeong Kim designed a snake-shaped graphene-gold mesh double-layer composite sweat sensing electrode, which not only has higher electrochemical activity, but also improves the mechanical deformation ability of the electrode through the snake-shaped structure, thereby adapting to the large deformation characteristics of the skin [Nature Nanotechnology, 2016, 11(6): 566-572], but it is difficult to apply to porous fiber substrates. Invention patent CN114295698A discloses a new fiber-type sweat ion detection sensor and its preparation method, which uses multi-walled carbon nanotubes as the conductive core and liquid metal as the conductive layer. Although it improves the anti-deformation ability, it is difficult to apply it on the skin surface, and the conformal ability needs to be improved.
[0005] In summary, although flexible wearable sweat detection sensors can achieve non-invasive, real-time and continuous monitoring of physiological information at the molecular level, existing wearable surface sweat sensors still face the following problems: (1) It is difficult to achieve long-term sustainable monitoring, such as poor air permeability causing inflammation; (2) The dynamic characteristics are poor and it is difficult to adapt to soft and highly deformable skin, resulting in unstable transmission of detection signals during exercise; (3) It is difficult to achieve unidirectional penetration / conduction of sweat, thereby unidirectionally collecting trace amounts of sweat and preventing cross-contamination between new and old sweat to ensure detection accuracy. Summary of the invention
[0006] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a sensor for in-situ detection of sweat on the body surface based on composite nanofibers and a preparation method thereof. In view of the difficulties in sweat collection in the current wearable sweat detection technology, such as difficulty in achieving directional transport of sweat, and difficulty in adapting to soft skin, signal transmission instability is prone to occur in sports scenes, the present invention prepares composite nanofibers with a gradient wettability structure, and utilizes its capillary siphon effect to achieve unidirectional transmission of sweat, which not only solves the cross-contamination caused by the accumulation of new and old sweat, but also can separate the sensing electrode from the skin and the external environment, thereby reducing the risk of sweat contamination while achieving unidirectional transmission of sweat; on the other hand, liquid metal alloy is used as a signal transmission electrode, which has both high conductivity and ductility, ensuring the stability of signal transmission during bending and stretching.
[0007] The technical solution of the present invention is as follows:
[0008] The first aspect of the present invention provides a sensor for in-situ detection of sweat on the body surface based on composite nanofibers, comprising a flexible substrate and a detection electrode;
[0009] Wherein, the flexible substrate comprises:
[0010] Hydrophobic layer;
[0011] a liquid-conducting layer, arranged on the hydrophobic layer, the liquid-conducting layer having a sweat non-wetting area and a first sweat wetting area, the contact angle of the first sweat wetting area gradually decreases from close to the hydrophobic layer to away from the hydrophobic layer, and the contact angle of the first sweat wetting area close to the hydrophobic layer is smaller than the contact angle of the hydrophobic layer;
[0012] A liquid collection layer, disposed on the liquid conducting layer, the liquid collection layer having a sweat non-wetting area and a second sweat wetting area, wherein a contact angle of the second sweat wetting area is smaller than a contact angle of the first sweat wetting area away from the hydrophobic layer;
[0013] a volatile layer disposed on the liquid collection layer, wherein the volatile layer has a third sweat wetting area, wherein a contact angle of the third sweat wetting area is greater than a contact angle of the second sweat wetting area and is smaller than a contact angle of the first sweat wetting area on a side away from the hydrophobic layer;
[0014] The detection electrode is disposed in the liquid collection layer and contacts the second sweat wetting area.
[0015] Optionally, the contact angle is a contact angle to sweat.
[0016] Optionally, the liquid conducting layer, the liquid collecting layer and the volatile layer are all nanofiber membranes;
[0017] The surface energy of the nanofiber membrane in the first sweat wetted area gradually increases from close to the hydrophobic layer to far away from the hydrophobic layer, the fiber diameter of the nanofiber membrane in the first sweat wetted area gradually increases from close to the hydrophobic layer to far away from the hydrophobic layer, and the size of the gaps between the fibers gradually decreases from close to the hydrophobic layer to far away from the hydrophobic layer;
[0018] The surface energy of the nanofiber membrane in the second sweat wetted area is less than the surface energy of the nanofiber membrane on the side of the first sweat wetted area away from the hydrophobic layer;
[0019] The surface energy of the nanofiber membrane in the third sweat wetting area is greater than the surface energy of the nanofiber membrane in the second sweat wetting area, and is less than the surface energy of the nanofiber membrane in the first sweat wetting area away from the hydrophobic layer.
[0020] Optionally, the detection electrode comprises:
[0021] An electrode deposition layer is arranged on a side of the liquid collection layer close to the liquid conducting layer, and one end of the electrode deposition layer is in contact with the second sweat wetting area;
[0022] a sensing electrode, disposed on the electrode deposition layer and in contact with the second sweat wetting area;
[0023] A signal transmission electrode is arranged at one end of the electrode deposition layer away from the second sweat wetting area;
[0024] Wherein, the contact angle of the electrode deposition layer to sweat is smaller than the contact angle of the sensing electrode.
[0025] Optionally, the contact angle of the hydrophobic layer to sweat is 140-150°
[0026] The contact angle of the first sweat-wetting area on the side close to the hydrophobic layer to the sweat is 40-50°, and the contact angle of the first sweat-wetting area on the side away from the hydrophobic layer to the sweat is 20-30°;
[0027] The contact angle of the second sweat-wetting area to sweat is 14-16°;
[0028] The contact angle of the third sweat wetting area to sweat is 17-19°;
[0029] The contact angle of the electrode deposition layer to the liquid metal is 20-30°;
[0030] The area of the third sweat wetting zone is greater than that of the second sweat wetting zone.
[0031] The second aspect of the present invention provides a method for preparing a sensor for in-situ detection of sweat on the body surface based on composite nanofibers, comprising the following steps:
[0032] preparing an electrode deposition layer;
[0033] preparing a sensing electrode on the electrode deposition layer;
[0034] Depositing a nanofiber membrane with a uniform structure on the sensing electrode, modifying the wettability of a local area of the nanofiber membrane to form a second sweat wetting area, and obtaining a liquid collection layer;
[0035] Depositing a nanofiber membrane with a uniform structure on the liquid collection layer, modifying the wettability of a local area or the entire area of the nanofiber membrane to form a third sweat wetting area, and obtaining a volatile layer;
[0036] removing the electrode deposition layer, the sensing electrode, the liquid collection layer and the volatile layer, and preparing a signal transmission electrode on the electrode deposition layer;
[0037] A nanofiber membrane is deposited on a side of the liquid collection layer away from the volatile layer, the diameter and pores of the nanofibers are regulated by an electrospinning process, and the wettability of a local area of the nanofiber membrane is modified by combining a mask and laser modification to form a first sweat wetting area, thereby obtaining a liquid conducting layer;
[0038] A nanofiber membrane is deposited on a side of the liquid-conducting layer away from the liquid-collecting layer to obtain a hydrophobic layer.
[0039] Optionally, a graphene oxide / TPU composite nanofiber membrane is formed on a silicon wafer by an electrostatic direct writing process to prepare an electrode deposition layer;
[0040] Prepare sensing electrodes on the electrode deposition layer by screen printing, wherein the sensing electrodes include a counter electrode, a reference electrode and a working electrode;
[0041] Depositing a nanofiber membrane with a uniform structure on the sensing electrode by an electrospinning process, and modifying the wettability of a local area of the nanofiber membrane by combining a mask and laser modification to form a second sweat wetting area, thereby obtaining a liquid collection layer;
[0042] Depositing a uniformly structured nanofiber membrane on the prepared liquid collection layer by an electrospinning process, and modifying the wettability of a local area or the entire area of the nanofiber membrane by combining a mask and laser modification to form a third sweat wetting area, thereby obtaining a volatile layer;
[0043] The electrode deposition layer, the sensing electrode, the liquid collection layer and the volatile layer are removed from the silicon wafer, and a liquid metal alloy is formed on the electrode deposition layer by a transfer process to obtain a signal transmission electrode;
[0044] A nanofiber membrane is deposited on the side of the liquid collection layer away from the volatile layer, the diameter and pores of the nanofibers are regulated by an electrostatic spinning process, and the wettability of a local area of the nanofiber membrane is modified by combining a mask and laser modification to form a first sweat wetting area, thereby obtaining a liquid conducting layer; wherein the surface energy gradient of the nanofiber membrane is obtained by controlling the laser treatment time, and the diameter and pores of the nanofibers are regulated by the applied spinning voltage, the spinning deposition spacing, and the liquid supply rate;
[0045] A nanofiber membrane is deposited on a side of the liquid-conducting layer away from the liquid-collecting layer, and the diameter and pores of the nanofibers are regulated by an electrostatic spinning process to obtain a hydrophobic layer.
[0046] Optionally, the step of preparing the electrode deposition layer specifically includes:
[0047] The graphene oxide powder solution is dispersed in a solvent, and TPU particles are added to mix to obtain a GO / TPU composite precursor solution; the prepared GO / TPU composite precursor solution is used to prepare a GO / TPU composite nanofiber membrane on a silicon wafer surface by an electrostatic direct writing process to prepare an electrode deposition layer;
[0048] The step of preparing the sensing electrode on the electrode deposition layer specifically includes:
[0049] Ag / AgCl reference electrode is prepared by screen printing Ag / AgCl ink and drying; counter electrode is prepared by screen printing carbon conductive ink; working electrode is prepared by screen printing carbon conductive ink, glucose oxidase solution is added dropwise to the working electrode area to make glucose oxidase adhere to the surface of the working electrode, and sensing electrode is obtained;
[0050] The steps of obtaining the liquid collection layer specifically include:
[0051] The TPU particles are dissolved in a solvent to obtain a TPU precursor solution; PVPK-90, P407 and a photoinitiator are dissolved to obtain a PVPK-90 / P407 solution; the TPU precursor solution is made into pure TPU nanofibers by electrostatic spinning, and the PVPK-90 / P407 solution is sprayed on a local area of the surface of the pure TPU nanofibers by an electrostatic spray process; a second sweat wetting area is formed by a mask and ultraviolet light irradiation, and a sweat non-wetting area is formed in an area not irradiated with ultraviolet light to obtain a liquid collection layer;
[0052] The steps of obtaining the volatile layer specifically include:
[0053] The TPU particles are dissolved in a solvent to obtain a TPU precursor solution; PVPK-90, P407 and a photoinitiator are dissolved to obtain a PVPK-90 / P407 solution; the TPU precursor solution is made into pure TPU nanofibers by electrostatic spinning, and the PVPK-90 / P407 solution is sprayed on a local area or the entire area of the surface of the pure TPU nanofibers by an electrostatic spray process; a third sweat wetting area is formed by a mask and ultraviolet light irradiation to obtain a volatile layer;
[0054] The steps of obtaining the signal transmission electrode specifically include:
[0055] The electrode deposition layer, the sensing electrode, the liquid collection layer and the volatile layer are removed from the silicon wafer, and a liquid metal alloy is formed on the electrode deposition layer by a transfer process to obtain a signal transmission electrode; wherein the liquid metal alloy is a gallium-indium-tin liquid alloy;
[0056] The steps of obtaining the liquid conducting layer specifically include:
[0057] The TPU particles are dissolved in a solvent to obtain a TPU precursor solution; PVPK-90, P407 and a photoinitiator are dissolved to obtain a PVPK-90 / P407 solution; the TPU precursor solution is made into pure TPU nanofibers by reducing the electrospinning voltage at an interval of electrostatic spinning; and the PVPK-90 / P407 solution is sprayed on a local area of the surface of the pure TPU nanofibers at an interval of an electrostatic spray process, wherein the mass ratio of PVPK-90 to P407 in the PVPK-90 / P407 solution gradually increases; a first sweat wetting area is formed by a mask and ultraviolet light irradiation, and a sweat non-wetting area is formed in an area not irradiated with ultraviolet light to obtain a liquid conducting layer;
[0058] The steps of obtaining the hydrophobic layer specifically include:
[0059] The TPU particles are dissolved in a solvent to obtain a TPU precursor solution; the TPU precursor solution is made into pure TPU nanofibers by electrospinning to obtain a hydrophobic layer.
[0060] Optionally, in the step of preparing the electrode deposition layer, the mass ratio of the graphene oxide powder solution, the solvent and the TPU particles is 0.008-0.012:1.8-2.2:0.8-1, and the electrostatic direct writing process parameters include: the direct writing voltage is 1.8-2.2 kV, the liquid supply rate is 145-155 uL / h, and the direct writing distance is 1.4-1.6 cm;
[0061] In the step of obtaining the liquid collection layer, the mass ratio of the solvent to the TPU particles is 1.8-2.2:0.8-1, the mass ratio of PVPK-90 to P407 is 1:3.8-1:4.2, the electrospinning voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, the spinning spacing is 14-16 cm, the spray voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, and the spray spacing is 14-16 cm;
[0062] In the step of obtaining the volatile layer, the mass ratio of the solvent to the TPU particles is 1.8-2.2:0.8-1, the mass ratio of PVPK-90 to P407 is 1:2.8-1:3.2, the electrospinning voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, the spinning spacing is 14-16 cm, the spray voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, and the spray spacing is 14-16 cm;
[0063] In the step of obtaining a signal transmission electrode, the mass ratio of gallium:indium:tin is 0.68:0.215:0.1;
[0064] In the step of obtaining the hydrophobic layer, the mass ratio of the solvent to the TPU particles is 1.8~2.2:0.8~1, the electrospinning voltage is 18~22 kV, the liquid supply rate is 280~320 uL / h, and the spinning spacing is 14~16 cm.
[0065] Optionally, in the step of obtaining the liquid conducting layer 12,
[0066] The initial electrospinning voltage was 18-22 kV, and the electrospinning voltage was reduced by 2.5-3.5 kV every 10-25 min. The liquid supply rate was 280-320 uL / h, and the spinning spacing was 14-16 cm.
[0067] Each interval was 14-16 min, the mass ratio of PVPK-90 and P407 in the PVPK-90 / P407 solution gradually increased from 1:3.8-1:4.2 to 2.8:1-3.2:1, the spray voltage was 18-22 kV, the liquid supply rate was 180-220 uL / h, and the spray spacing was 14-16 cm.
[0068] Optionally, the mass ratios of PVPK-90 and P407 in the PVPK-90 / P407 solution are 1:4, 1:3, 1:2, 1:1, 2:1, and 3:1, respectively.
[0069] The present invention has at least one of the following beneficial effects:
[0070] (1) The present invention has a porous nanofiber structure as a whole, good flexibility, and can adapt to the deformation of the skin; it has good air permeability and ensures long-term wearing comfort;
[0071] (2) The present invention makes full use of the multi-scale structure of electrospun nanofibers to achieve unidirectional self-permeation of sweat, prevent cross-contamination between new and old sweat, and improve the accuracy of sweat detection;
[0072] (3) The present invention uses liquid metal as a signal transmission electrode to ensure the stability of the detection signal transmission under deformation and improve the anti-interference ability of the sweat detection signal. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is a schematic structural diagram of a sensor for in-situ detection of sweat on the body surface based on composite nanofibers in an embodiment of the present invention;
[0074] Figure 2 It is a flowchart of a method for preparing a sensor for in-situ detection of body surface sweat based on composite nanofibers in an embodiment of the present invention;
[0075] Figure 3 The test results of Example 1 of the present invention are as follows;
[0076] Figure 4 The test results of Example 2 of the present invention are as follows;
[0077] Figure 5 This is the test result of Example 3 of the present invention.
[0078] The markings in the accompanying drawings are: 1. flexible substrate; 2. detection electrode; 11. hydrophobic layer; 12. liquid conducting layer; 121. first sweat wetting area; 13. liquid collecting layer; 131. second sweat wetting area; 14. volatile layer; 141. third sweat wetting area; 21. sensing electrode; 22. signal transmission electrode; 23. electrode deposition layer. DETAILED DESCRIPTION
[0079] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0080] An embodiment of the present invention provides a sensor for in-situ detection of sweat on the body surface based on composite nanofibers, such as Figure 1 As shown, it includes a flexible substrate 1 and a detection electrode 2 .
[0081] The flexible substrate 1 is prepared by layer-by-layer deposition through an electrospinning process, and is not only flexible and can be conformally adhered to the skin surface, but also has an overall porous structure and good air permeability, and will not cause inflammation when worn for a long time.
[0082] Furthermore, the flexible substrate 1 comprises: a hydrophobic layer 11 , a liquid conducting layer 12 , a liquid collecting layer 13 and a volatile layer 14 .
[0083] The hydrophobic layer 11 is in direct contact with the skin and has a non-wetting property to sweat, thereby ensuring that sweat will not be retained at the interface between the sweat detection sensor and the skin during wearing, thereby improving wearing comfort.
[0084] The liquid-conducting layer 12 is located on the hydrophobic layer 11, and the local area (such as Figure 1 The first sweat wetting area 121 in the middle maintains wettability to sweat and has a gradient wetting property to sweat in the longitudinal direction; after the sweat penetrates through the hydrophobic layer 11 under the action of sweat gland secretion pressure, it spontaneously penetrates from the liquid conducting layer 12 to the liquid collecting layer 13 under the action of capillary force.
[0085] Furthermore, the gradient wetting property of the liquid-conducting layer 12 can be obtained by any method of gradient diameter, gradient pore size, gradient surface energy of the composite nanofibers, or a combination thereof.
[0086] Furthermore, the nanofiber gradient diameter and gradient pore size of the liquid-conducting layer 12 can be constructed by regulating an electrospinning process, and the electrospinning process can be but is not limited to the spinning applied voltage, spinning deposition spacing, liquid supply rate, and combinations thereof.
[0087] Furthermore, the gradient surface energy of the liquid-conducting layer 12 can be regulated and constructed by a surface modification process, and the surface modification process can be, but is not limited to, modifying the surface of the nanofibers by photografting hydrophilic substances with ultraviolet light.
[0088] The liquid collecting layer 13 is located above the liquid conducting layer 12, and the local area (such as Figure 1 The second sweat wetting area 131 has uniform wetting properties for sweat. When the sweat penetrates from the liquid conducting layer 12, it ensures that the sweat to be detected is in full contact with the detection electrode 2, thereby improving the detection accuracy.
[0089] The liquid conducting layer 12 and the liquid collecting layer 13 have a local area (such as Figure 1 The first sweat-wetting area 121 and the second sweat-wetting area 131 can be obtained by modifying the surface of the nanofiber by grafting hydrophilic substances through a mask combined with ultraviolet light treatment technology.
[0090] In addition to the first sweat wetting area 121 and the second sweat wetting area 131 having uniform wetting properties for sweat, the liquid conducting layer 12 and the liquid collecting layer 13 also have a sweat non-wetting area that is not wetted by sweat, thereby improving the directional permeability of sweat and the sensing accuracy. Figure 1As shown, the first sweat wetting area 121 and the second sweat wetting area 131 are respectively located in the middle of the liquid conducting layer 12 and the liquid collecting layer 13, and the sweat non-wetting areas are respectively located on both sides of the first sweat wetting area 121 and the second sweat wetting area 131.
[0091] The liquid-conducting layer 12 is a nanofiber membrane, and the surface energy of the nanofiber membrane in the first sweat wetting area 121 gradually increases from close to the hydrophobic layer 11 to far away from the hydrophobic layer 11, the fiber diameter of the nanofiber membrane in the first sweat wetting area 121 gradually increases from close to the hydrophobic layer 11 to far away from the hydrophobic layer 11, and the size of the gaps between the fibers gradually decreases from close to the hydrophobic layer 11 to far away from the hydrophobic layer 11;
[0092] In some embodiments, the diameter of the fiber gradually changes from 900-910 nm to 1.5-2.5 μm from close to the hydrophobic layer 11 to far away from the hydrophobic layer 11 .
[0093] The volatile layer 14 is located above the liquid collection layer 13 , and has a third sweat wetting area 141 thereon. The third sweat wetting area 141 may be the entire area of the volatile layer 14 or a local area. The area of the third sweat wetting area 141 is greater than that of the second sweat wetting area 131 .
[0094] In some embodiments, the third sweat wetting area 141 is the entire area of the volatile layer 14 , that is, the entire area of the volatile layer 14 remains wettable to sweat, increasing the contact area between sweat and air and accelerating the volatilization of old sweat.
[0095] Furthermore, the volatile layer 14 has better wettability to sweat than the liquid conducting layer 12, ensuring that the sweat detected in the liquid collecting layer 13 will only permeate into the volatile layer 14 in one direction due to the difference in capillary force, thereby preventing cross contamination between new and old sweat.
[0096] Furthermore, the difference in wettability of the volatile layer 14 and the liquid-conducting layer 12 to sweat can be obtained by any method of difference in diameter, pore size or surface energy of the composite nanofibers, or by a combination thereof.
[0097] Furthermore, the difference in nanofiber diameter and pore size between the volatile layer 14 and the liquid-conducting layer 12 can be constructed by regulating an electrospinning process, and the electrospinning process can be but is not limited to the spinning applied voltage, spinning deposition spacing, liquid supply rate, and combinations thereof.
[0098] Furthermore, the surface energy of the volatile layer 14 and the liquid-conducting layer 12 can be regulated and constructed by a surface modification process, and the surface modification process can be, but is not limited to, modifying the surface of the nanofibers by ultraviolet light grafting hydrophilic substances.
[0099] The detection electrode 2 includes a sensing electrode 21 , a signal transmission electrode 22 and an electrode deposition layer 23 , and is located below the liquid collection layer 13 and above the liquid conducting layer 12 .
[0100] The sensing electrode 21 is located on the electrode deposition layer 23 and is within the local range where the liquid collection layer 13 has uniform wetting properties for sweat, ensuring that the sweat that penetrates into the liquid collection layer 13 can fully contact the sensing electrode 21 .
[0101] The sensing electrode 21 may be a two-electrode system or a three-electrode system, and a three-electrode system is preferably selected in the embodiment.
[0102] The sensing electrode 21 is a two-electrode system including a working electrode and a reference electrode.
[0103] The sensing electrode 21 is a three-electrode system including a working electrode, a reference electrode and a counter electrode.
[0104] The signal transmission electrode 22 is located above the electrode deposition layer 23, outside the local area where the liquid collection layer 13 has uniform wetting properties for sweat, ensuring that the sweat that penetrates into the liquid collection layer 13 does not contact the signal transmission electrode 22, avoiding interference in the signal transmission process.
[0105] The signal transmission electrode 22 is liquid metal, which has high conductivity and ductility, shields the influence of skin deformation on the signal, and improves the signal's anti-interference ability.
[0106] The electrode deposition layer 23 has wettability to liquid metal and can deposit a patterned liquid metal structure; the other parts of the nanofibers mentioned in the present invention have no wettability to liquid metal, ensuring that the structure of the signal transmission electrode 22 is not destroyed during the deformation process, thereby improving the stability of the detection signal transmission.
[0107] The present invention also provides a method for preparing the above-mentioned composite nanofiber-based in-situ detection sensor for body surface sweat, comprising the following steps:
[0108] S1. Prepare an electrode deposition layer 23 on a silicon wafer by an electrostatic direct writing process. First, TPU particles are magnetically stirred and dissolved in dimethylacetamide (DMAC) to prepare a TPU precursor solution, and then an electrode deposition layer 23 with a certain pattern structure is prepared on the silicon wafer by electrostatic direct writing. The pattern features are determined according to the structures of the sensing electrode 21 and the signal transmission electrode 22.
[0109] S2, preparing the sensing electrode 21 on the electrode deposition layer 23 by screen printing process;
[0110] S3. A nanofiber membrane with a uniform structure is deposited on the detection electrode 2 prepared above by an electrospinning process, and the wettability of the local area is modified by combining a mask plate and laser modification to obtain a liquid collection layer 13; wherein the fiber surface energy gradient can be obtained by the laser treatment time, and the nanofiber diameter, pore and other dimensions can be regulated by process parameters such as the spinning applied voltage, the spinning deposition spacing and the liquid supply rate.
[0111] S4, depositing a uniform structure nanofiber membrane on the prepared liquid collection layer 13 through an electrospinning process, modifying the wettability of a local area or the entire area of the deposited uniform structure nanofiber membrane in combination with a mask and laser modification, and finally obtaining a volatile layer 14.
[0112] S5, peeling off the deposited film layer from the silicon wafer, and then preparing a liquid metal pattern on the electrode deposition layer 23 by a transfer process to obtain a signal transmission electrode 22:
[0113] S6. Deposit a multi-scale composite nanofiber membrane on the peeled side of the polysilicon wafer with the liquid metal transport electrode 22 prepared above (below the detection electrode 2), and control the diameter, pores and other dimensions of the deposited nanofibers through parameters such as the spinning applied voltage, spinning deposition spacing and liquid supply rate of the electrospinning process, and modify the wettability of the local area by combining the mask and laser modification to obtain a liquid conductive layer 12, wherein the surface energy gradient can be obtained by the laser treatment time.
[0114] S7. Continue to deposit a multi-scale composite nanofiber membrane under the above-mentioned liquid conductive layer 12, and adjust the diameter, pores and other dimensions of the deposited nanofibers by parameters such as the spinning applied voltage, spinning deposition spacing and liquid supply rate of the electrospinning process, and obtain the hydrophobic layer 11 without any surface treatment.
[0115] The present invention uses composite nanofibers and liquid metal to construct a flexible electrochemical sensor for in-situ detection of sweat on the body surface, wherein the composite nanofibers play the role of sweat extraction and collection, and realize the one-way controllable collection and diversion of sweat through the gradient wettability characteristics, and can prevent the reflux of sweat from causing the mixing of new and old sweat; wherein the liquid metal is used to construct a signal transmission electrode, which can adapt to the soft and highly deformable human skin, and can ensure the stable transmission of physiological signals even during exercise. Finally, the sensor as a whole is a porous fiber structure, which has good flexibility and air permeability, and will not cause inflammation and other problems when worn for a long time.
[0116] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0117] Example 1
[0118] This embodiment provides a sensor for in-situ detection of sweat on the body surface based on composite nanofibers and a preparation method thereof, such as Figure 1 As shown, the in-situ detection sensor for sweat on the body surface comprises:
[0119] The hydrophobic layer 11 is made of a pure thermoplastic polyurethane (TPU) nanofiber membrane of uniform size, which is not wetted by sweat, and the sweat contact angle is measured to be 146°;
[0120] The liquid-conducting layer 12 is made of a multi-scale TPU composite nanofiber membrane. The fiber diameter of the multi-scale TPU composite nanofiber membrane has a gradient characteristic (gradually changing from 905 nm at the bottom to 2 μm at the top), and the local area of the multi-scale TPU composite nanofiber membrane (such as Figure 1 The fiber surface of the first sweat wetting area 121 in the liquid conductive layer 12 has a gradient surface energy characteristic (hydrophilic polyvinyl pyrrolidone K-90 (PVPK-90) / poloxamer 407 (P407) is grafted by ultraviolet light, and the wettability of the upper part is better than that of the lower part by changing the proportion of P407). Under the combined influence, the upper part of the liquid conductive layer 12 grafted with PVPK-90 / P407 by ultraviolet light (the side of the first sweat wetting area 121 away from the hydrophobic layer 11) has a sweat contact angle of 24°, and the lower part of the liquid conductive layer 12 grafted with PVPK-90 / P407 by ultraviolet light (the side of the first sweat wetting area 121 close to the hydrophobic layer 11) has a sweat contact angle of 42°, while the sweat contact angle of the area not grafted with PVPK-90 / P407 by ultraviolet light (sweat non-wetting area) is measured to be greater than 132°.
[0121] The liquid collection layer 13 is made of a uniform-scale TPU composite nanofiber membrane, and the local area of the uniform-scale TPU composite nanofiber membrane (such as Figure 1 The second sweat wetting area 131) is grafted with hydrophilic PVPK-90 / P407 by ultraviolet light, and the wettability of the hydrophilically treated area to sweat remains uniform, and is better than the upper part of the liquid-conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light. The contact angle is measured to be 16°, and the contact angle of the area not grafted with PVPK-90 / P407 by ultraviolet light (sweat non-wetting area) to sweat is measured to be greater than 130°.
[0122] The volatile layer 14 is made of a uniform-sized TPU composite nanofiber membrane, the entire area of which is grafted with hydrophilic PVPK-90 / P407 by ultraviolet light, and the wettability to sweat after hydrophilic treatment is worse than that of the liquid collection layer 13, but better than the upper part of the liquid conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light, and the contact angle is measured to be 20°.
[0123] The sensing electrode 21, in this embodiment, adopts a three-electrode system for glucose detection, including a counter electrode, a reference electrode and a working electrode. The reference electrode is Ag / AgCl, the counter electrode is a solidified carbon conductive ink, and the working electrode is a carbon conductive ink modified with glucose oxidase.
[0124] The signal transmission electrode 22 is made of a liquid metal alloy pattern, wherein the mass ratio of gallium:indium:tin in the liquid metal alloy is 0.68:0.215:0.1, and the melting point is 11°C.
[0125] The electrode deposition layer 23 is made of a graphene oxide (GO) / TPU composite nanofiber membrane with a patterned structure and uniform scale. It wets the liquid metal and the contact angle is measured to be 26°. Other nanofiber membranes of the present invention do not wet the liquid metal and the contact angle is measured to be greater than 137°.
[0126] like Figure 2 As shown, the preparation method of the in-situ detection sensor for body surface sweat comprises the following steps:
[0127] S1. Preparation of electrode deposition layer 23: 0.01 g GO powder solution was dissolved in 2 g dimethylacetamide (DMAC) solvent by ultrasound, and then 0.9 g TPU particles were added, and finally magnetic stirring was performed for 3 hours to obtain GO / TPU composite precursor solution; the prepared GO / TPU composite precursor solution was loaded into a syringe, and a patterned GO / TPU composite nanofiber membrane was prepared on the surface of a silicon wafer by an electrostatic direct writing process (2 kV direct writing voltage, 150 uL / h liquid supply rate, 1.5 cm direct writing distance), thereby preparing the electrode deposition layer 23. The pattern of the electrode deposition layer 23 can be obtained by the desired pattern from the direct writing substrate motion path.
[0128] S2. Preparation of sensing electrode 21: First, Ag / AgCl ink is screen-printed and dried to obtain Ag / AgCl reference electrode; the counter electrode is prepared by screen-printing carbon conductive ink; the working electrode is first prepared by screen-printing carbon conductive ink, 100uL glucose oxidase solution is added to the working electrode area by a pipette, and the above operation is repeated 5 times after drying at room temperature, so that the glucose oxidase is completely attached to the surface of the working electrode. The preparation method of glucose oxidase solution is: 40 mg of glucose oxidase powder is fully dissolved in 50ml phosphate buffer (PBS).
[0129] S3, preparation of liquid collection layer 13: 0.9 g of TPU particles were dissolved in 2 g of DMAC solvent by magnetic stirring for 3 h, and the obtained TPU precursor solution was loaded into a syringe; PVPK-90, P407 and photoinitiator 6967 were fully dissolved by a constant temperature (80 ° C) magnetic stirrer to obtain a PVPK-90 / P407 solution, and the mass ratio of PVPK-90, P407 and photoinitiator 6967 was 1:4:3; the TPU precursor solution was then used to prepare pure TPU nanofibers by electrostatic spinning, and the PVPK-90 / P407 solution was sprayed on the surface of the pure TPU nanofibers prepared above by an electrostatic spray process during spinning to form a second sweat wetting area 131; finally, a mask and ultraviolet light (wavelength 568.7 nm) irradiation for 4 minutes, after curing, hydrophilic TPU nanofibers can be obtained in the irradiated area, and the other parts are not wetted by sweat because they are not treated with ultraviolet light, forming a sweat non-wetting area. During the spinning process, the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, and the spinning spacing is 15 cm, so that hydrophobic TPU nanofibers with uniform fiber diameter can be obtained; for hydrophilic TPU nanofibers, while electrospinning TPU nanofibers, PVPK-90 / P407 solution is electrostatically sprayed, the spray voltage is 20 kV, the liquid supply rate is 200 uL / h, the spray spacing is 15 cm, and finally treated with ultraviolet light.
[0130] S4, preparation of the volatile layer 14: electrospinning and depositing pure TPU nanofibers on the above-mentioned liquid collection layer 13, and at the same time electrostatically spraying a PVPK-90 / P407 solution, wherein the mass ratio of PVPK-90:P407:photoinitiator is 1:3:3; then the entire fiber membrane is irradiated with ultraviolet light (wavelength of 568.7 nm) for 4 minutes, and hydrophilic TPU nanofibers can be obtained after curing; the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, the spinning spacing is 15 cm, the spray voltage is 20 kV, the liquid supply rate is 200 uL / h, and the spray spacing is 15 cm.
[0131] S5. Preparation of the signal transmission electrode 22: The electrode deposition layer 23, the sensing electrode 21, the liquid collection layer 13 and the volatile layer 14 prepared on the silicon wafer are removed from the silicon wafer, and then the liquid metal alloy is adhered to the electrode deposition layer 23 by a transfer method. Since the electrode deposition layer 23 wets the liquid metal alloy (the contact angle is measured to be 26°), and the sensing electrode 21 does not wet the liquid metal (the contact angle is measured to be 136°), the liquid metal alloy will automatically adhere to the electrode deposition layer 23. The reason why the liquid metal alloy adheres to the GO / TPU composite nanofiber membrane is that GO is rich in -OH functional groups and adheres to the liquid metal Ga2O3 oxide layer through hydrogen bonds.
[0132] S6. Preparation of liquid-conducting layer 12: peeling the composite film prepared above from the silicon wafer, and then electrospinning and depositing multi-scale TPU composite nanofibers on the peeled surface, and at the same time electrostatically spraying PVPK-90 / P407 solution, and finally irradiating with ultraviolet light (wavelength of 568.7 nm) through a mask for 4 minutes. After curing, hydrophilic TPU nanofibers can be obtained in the irradiated area, and the other parts are not wetted by sweat because they are not treated with ultraviolet light. During the spinning process, the electrospinning voltage was initially 20 kV, the liquid supply rate was 300 uL / h, and the spinning spacing was 15 cm. Then, the electrospinning voltage was reduced by 3 kV every 15 min, so that multi-scale fibers with gradually increasing fiber diameters from bottom to top could be obtained. While electrospinning TPU nanofibers, PVPK-90 / P407 solution was electrostatically sprayed. The initial mass ratio of PVPK-90:P407:photoinitiator was 1:4:3. Then, every 15 min, the mass ratio of the photoinitiator remained unchanged, and the mass ratio of PVPK-90:P407 decreased in sequence from 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, etc. The spray voltage was 20 kV, the liquid supply rate was 200 uL / h, and the spray spacing was 15 cm.
[0133] S7. Preparation of the hydrophobic layer 11: The prepared liquid-conducting layer 12 is electrospun to deposit uniform-sized TPU composite nanofibers. During the spinning process, the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, and the spinning spacing is 15 cm. Since the hydrophobic layer 11 is not grafted with PVPK-90 / P407 by ultraviolet light, it is not wetted by sweat.
[0134] Under the action of the secretion pressure of the sweat glands of the skin and the hydrophilic capillary force of the hydrophobic layer 11 and the liquid-conducting layer 12, the sweat will be self-driven by the hydrophobic layer 11 to penetrate into the liquid-conducting layer 12. Because the hydrophobic layer 11 does not wet sweat, no sweat will remain on the contact surface with the skin, maintaining long-term wearing comfort; the liquid-conducting layer 12 has a gradient fiber diameter and a gradient surface energy. Under the action of Laplace pressure, the sweat will be self-driven to penetrate from the lower part of the liquid-conducting layer 12 to the upper part of the liquid-conducting layer 12, and then stay in the liquid collection layer 13 and fully contact with the detection electrode 2. The volatile layer 14 has a large volatile area, which ensures that the sweat after detection will evaporate in time to avoid cross-contamination between new and old sweat; on the other hand, in the sweat wetting area, the sweat contact angle of the volatile layer 14 is 20°, the contact angle of the liquid collecting layer 13 is 16°, and the contact angle of the upper part of the liquid conducting layer 12 is 24° and the lower part is 42°; the wettability of the liquid collecting layer 13 is better than that of the volatile layer 14, and the sweat will stay in the liquid collecting layer 13 to ensure that the sweat can fully contact the detection electrode 2; the wettability of the volatile layer 14 is better than that of the liquid conducting layer 12, which ensures that the detected sweat will not flow back and prevent cross-contamination between new and old sweat. The in-situ detection sensor for body surface sweat based on composite nanofibers provided in this embodiment has an overall porous structure with good air permeability, which avoids inflammation caused by long-term wear. In addition, the signal transmission electrode adopts liquid metal, which can ensure the stability of signal transmission under deformation interference. When sweat penetrates into the liquid collection layer 13, it will contact the sensing electrode 21. Under the action of glucose oxidase modified by the working electrode, the sweat will generate H2O2, which will cause the change of current.
[0135] In order to verify the feasibility and deformation resistance of the sensor, the current response of the sensor to different glucose concentrations in the initial state and the 30% stretched state was investigated. Figure 3 As shown, under the condition of constant voltage of -0.1V, the current change of the sensing electrode 21 shows a linear increasing relationship with the glucose concentration. When the glucose concentration increases from 0.05 mmol / L to 2.5 mmol / L, the current response increases from 0.51 uA to 4.32 uA. It can also be found that stretching has little effect on the current response. Under a 30% stretching state, when the glucose concentration increases from 0.05 mmol / L to 2.5 mmol / L, the current response increases from 0.56 uA to 4.42 uA, indicating that the liquid metal electrode has good signal transmission stability and can resist the influence of skin deformation on the sensing performance.
[0136] Example 2
[0137] This embodiment provides a sensor for in-situ detection of sweat on the body surface based on composite nanofibers and a preparation method thereof, such as Figure 1 The in-situ detection sensor for body surface sweat comprises:
[0138] The hydrophobic layer 11 is made of a uniformly sized pure thermoplastic polyurethane (TPU) nanofiber membrane and is not wetted by sweat, and the sweat contact angle is measured to be 146°.
[0139] The liquid-conducting layer 12 is made of a multi-scale TPU composite nanofiber membrane. The fiber diameter of the multi-scale TPU composite nanofiber membrane has a gradient characteristic (gradually changing from 905 nm at the bottom to 2 μm at the top), and the pore size also has a gradient characteristic (the pore structure at the bottom is larger than the pore structure at the top). Finally, the local area of the multi-scale TPU composite nanofiber membrane (such as Figure 1 In (such as Figure 1 The fiber surface of the first sweat wetting area 121) has a gradient surface energy characteristic (hydrophilic polyvinyl pyrrolidone K-90 (PVPK-90) / poloxamer 407 (P407) is grafted by ultraviolet light, and the wettability of the upper part is better than that of the lower part by changing the proportion of P407). Under the combined influence, the upper part of the liquid-conducting layer 12 grafted with PVPK-90 / P407 by ultraviolet light (the side of the first sweat wetting area 121 away from the hydrophobic layer 11) has a sweat contact angle of 20°, the lower part of the liquid-conducting layer 12 grafted with PVPK-90 / P407 by ultraviolet light (the side of the first sweat wetting area 121 close to the hydrophobic layer 11) has a sweat contact angle of 39°, and the sweat contact angle of the area not grafted with PVPK-90 / P407 by ultraviolet light is measured to be greater than 130°.
[0140] The liquid collection layer 13 is made of a uniform-scale TPU composite nanofiber membrane, and the local area of the uniform-scale TPU composite nanofiber membrane (such as Figure 1 The shaded part in the figure) is grafted with hydrophilic PVPK-90 / P407 by ultraviolet light, and the wettability of the hydrophilic treated area to sweat is uniform and better than that of the upper part of the liquid-conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light. The contact angle is measured to be 15°, and the contact angle of the area where PVPK-90 / P407 is not grafted by ultraviolet light is measured to be greater than 133°.
[0141] The volatile layer 14 is made of a uniform-sized TPU composite nanofiber membrane, the entire area of which is grafted with hydrophilic PVPK-90 / P407 by ultraviolet light, and the wettability to sweat after hydrophilic treatment is worse than that of the liquid collection layer 13, but better than the upper part of the liquid conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light, and the contact angle is measured to be 18°.
[0142] The sensing electrode 21, in this embodiment, adopts a three-electrode system for glucose detection, including a counter electrode, a reference electrode and a working electrode. The reference electrode is Ag / AgCl, the counter electrode is a solidified carbon conductive ink, and the working electrode is a carbon conductive ink modified with glucose oxidase.
[0143] The signal transmission electrode 22 is made of a liquid metal pattern, the mass ratio of gallium:indium:tin is 0.68:0.215:0.1, and the melting point is 11°C.
[0144] The electrode deposition layer 23 is made of a graphene oxide (GO) / TPU composite nanofiber membrane with a patterned structure and uniform scale. It wets the liquid metal and the contact angle is measured to be 26°. Other nanofiber membranes of the present invention do not wet the liquid metal and the contact angle is measured to be greater than 136°.
[0145] like Figure 2 As shown, the preparation method of the in-situ detection sensor for body surface sweat comprises the following steps:
[0146] S1. Preparation of electrode deposition layer 23: 0.01 g GO powder solution was dissolved in 2 g dimethylacetamide (DMAC) solvent by ultrasound, and then 0.9 g TPU particles were added, and finally magnetic stirring was performed for 3 hours to obtain GO / TPU composite precursor solution; the prepared GO / TPU composite precursor solution was loaded into a syringe, and a patterned GO / TPU composite nanofiber membrane was prepared on the surface of a silicon wafer by an electrostatic direct writing process (2 kV direct writing voltage, 150 uL / h liquid supply rate, 1.5 cm direct writing distance), thereby preparing the electrode deposition layer 23. The pattern of the electrode deposition layer 23 can be obtained by the desired pattern from the direct writing substrate motion path.
[0147] S2. Preparation of sensing electrode 21: First, Ag / AgCl ink is screen-printed and dried to obtain Ag / AgCl reference electrode; the counter electrode is prepared by screen-printing carbon conductive ink; the working electrode is first prepared by screen-printing carbon conductive ink, 100uL glucose oxidase solution is added to the working electrode area by a pipette gun, and the above operation is repeated 5 times after drying at room temperature, so that glucose oxidase is completely attached to the surface of the working electrode. The preparation method of glucose oxidase solution is: 40mg glucose oxidase powder is fully dissolved in 50ml PBS solution.
[0148] S3, preparation of liquid collection layer 13: 0.9 g of TPU particles were dissolved in 2 g of DMAC solvent by magnetic stirring for 3 h, and the obtained TPU precursor solution was loaded into a syringe; PVPK-90, P407 and photoinitiator 6967 were fully dissolved by a constant temperature (80 ° C) magnetic stirrer to obtain a PVPK-90 / P407 solution, and the mass ratio of PVPK-90, P407 and photoinitiator was 1:4:3; then pure TPU nanofibers were prepared by electrostatic spinning of TPU precursor, and PVPK-90 / P407 solution was sprayed on the surface of the pure TPU nanofibers prepared above by electrostatic spraying process during spinning; finally, the mask and ultraviolet light (wavelength of 568.7 nm) were irradiated for 4 min, and hydrophilic TPU nanofibers were obtained in the irradiated area after curing, and the other parts were not wetted by sweat because they were not treated with ultraviolet light. During the spinning process, the electrospinning voltage was 20 kV, the liquid supply rate was 300 uL / h, and the spinning spacing was 15 cm, so that multi-scale TPU nanofibers with uniform fiber diameter could be obtained; while electrospinning TPU nanofibers, PVPK-90 / P407 solution was electrostatically sprayed, with a spray voltage of 20 kV, a liquid supply rate of 200 uL / h, and a spray spacing of 15 cm.
[0149] S4, preparation of volatile layer 14: electrospinning and depositing pure TPU nanofibers on the above-mentioned liquid collection layer 13, and at the same time electrostatically spraying PVPK-90 / P407 solution, wherein the mass ratio of PVPK-90:P407 is 1:3; then irradiating the entire fiber membrane with ultraviolet light (wavelength of 568.7 nm) for 4 minutes, and hydrophilic TPU nanofibers can be obtained after curing; the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, the spinning spacing is 15 cm, the spray voltage is 20 kV, the liquid supply rate is 200 uL / h, and the spray spacing is 15 cm.
[0150] S5. Preparation of the signal transmission electrode 22: The electrode deposition layer 23, the sensing electrode 21, the liquid collection layer 13 and the volatile layer 14 prepared on the silicon wafer are removed from the silicon wafer, and then the liquid metal alloy is adhered to the electrode deposition layer 23 by a transfer method. Since the electrode deposition layer 23 wets the liquid metal (the contact angle is measured to be 26°), and the sensing electrode 21 does not wet the liquid metal (the contact angle is measured to be 136°), the liquid metal will automatically adhere to the electrode deposition layer 23. The reason why the liquid metal adheres to the GO / TPU composite nanofiber membrane is that GO is rich in -OH functional groups and adheres to the liquid metal Ga2O3 oxide layer through hydrogen bonds.
[0151] S6, preparation of liquid-conducting layer 12: peel off the composite film prepared above from the silicon wafer, and then electrospin deposit multi-scale TPU composite nanofibers on the peeled surface, and electrostatically spray PVPK-90 / P407 solution at the same time, and finally irradiate for 4 minutes through a mask and ultraviolet light (wavelength of 568.7 nm). After curing, hydrophilic TPU nanofibers can be obtained in the irradiated area, and other parts are not wetted by sweat because they are not treated with ultraviolet light. In the spinning process, the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, and the spinning spacing is 15 cm; then every 15 minutes, the electrospinning voltage is reduced by 3 kV, so that multi-scale fibers with gradually increasing fiber diameters from bottom to top can be obtained; at the same time, every 15 minutes, the liquid supply rate is increased by 15 uL / h, the higher the rate, the faster the spinning jet is ejected, and the denser the fiber deposition is, so that multi-scale fibers with gradually decreasing pore structures from bottom to top can be obtained. While electrospinning TPU nanofibers, PVPK-90 / P407 solution was electrostatically sprayed. The initial mass ratio of PVPK-90:P407:photoinitiator was 1:4:3. Thereafter, every 15 min, the mass ratio of the photoinitiator remained unchanged, and the mass ratio of PVPK-90:P407 decreased in sequence of 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, etc. The spray voltage was 20 kV, the liquid supply rate was 200 uL / h, and the spray spacing was 15 cm.
[0152] S7. Preparation of the hydrophobic layer 11: The multi-scale TPU composite nanofibers were deposited on the liquid-conducting layer 12 prepared above by electrospinning. During the spinning process, the initial electrospinning voltage was 20 kV, the liquid supply rate was 300 uL / h, and the spinning spacing was 15 cm. Because the hydrophobic layer 11 was not grafted with PVPK-90 / P407 by ultraviolet light, it was not wetted by sweat.
[0153] Under the action of the secretion pressure of the sweat glands of the skin, the gradient capillary force of the hydrophobic layer 11 and the hydrophilic capillary force of the liquid conducting layer 12, the sweat will be self-driven by the hydrophobic layer 11 to penetrate into the liquid conducting layer 12. Because the hydrophobic layer 11 does not wet sweat, no sweat will remain on the contact surface with the skin, maintaining long-term wearing comfort; the liquid conducting layer 12 has a gradient fiber diameter and gradient surface energy. Under the action of Laplace pressure, the sweat will be self-driven to penetrate from the lower part of the liquid conducting layer 12 to the upper part of the liquid conducting layer 12, and then stay in the liquid collection layer 13 and fully contact with the detection electrode 2. The volatile layer 14 has a large volatile area, which ensures that the sweat after detection will evaporate in time to avoid cross-contamination between new and old sweat; on the other hand, in the sweat wetting area, the sweat contact angle of the volatile layer 14 is 18°, the contact angle of the liquid collecting layer 13 is 15°, and the upper contact angle of the liquid conducting layer 12 is 20° and the lower contact angle is 39°; the wettability of the liquid collecting layer 13 is better than that of the volatile layer 14, and the sweat will stay in the liquid collecting layer 13 to ensure that the sweat can fully contact the detection electrode 2; the wettability of the volatile layer 14 is better than that of the liquid conducting layer 12, which ensures that the detected sweat will not flow back and prevent cross-contamination between new and old sweat. The in-situ detection sensor for body surface sweat based on composite nanofibers provided in this embodiment has an overall porous structure with good air permeability, which avoids inflammation caused by long-term wear. In addition, the signal transmission electrode adopts liquid metal, which can ensure the stability of signal transmission under deformation interference. When sweat penetrates into the liquid collection layer 13, it will contact the sensing electrode 21. Under the action of glucose oxidase modified by the working electrode, the sweat will generate H2O2, which will cause the change of current.
[0154] In order to verify the feasibility and deformation resistance of the sensor, the current response of the sensor to different glucose concentrations in the initial state and the 30% stretched state was investigated. Figure 4 As shown, under the condition of constant voltage of -0.1V, the current change of the sensing electrode 21 shows a linear increasing relationship with the glucose concentration. When the glucose concentration increases from 0.05 mmol / L to 2.5 mmol / L, the current response increases from 0.55 uA to 4.25 uA. It can also be found that stretching has little effect on the current response. Under a 30% stretching state, when the glucose concentration increases from 0.05 mmol / L to 2.5 mmol / L, the current response increases from 0.57 uA to 4.36 uA, indicating that the liquid metal electrode has good signal transmission stability and can resist the influence of skin deformation on the sensing performance.
[0155] Example 3
[0156] This embodiment provides a sensor for in-situ detection of sweat on the body surface based on composite nanofibers and a preparation method thereof, such as Figure 1 The in-situ detection sensor for body surface sweat comprises:
[0157] The hydrophobic layer 11 is made of a pure TPU nanofiber membrane of uniform size and is not wetted by sweat. The sweat contact angle is measured to be 146°.
[0158] The liquid-conducting layer 12 is made of a multi-scale TPU composite nanofiber membrane. The fiber diameter of the multi-scale TPU composite nanofiber membrane has a gradient characteristic (gradually changing from 905 nm at the bottom to 2 μm at the top), and the pore size also has a gradient characteristic (the pore structure at the bottom is larger than the pore structure at the top). Finally, the local area of the multi-scale TPU composite nanofiber membrane (such as Figure 1 The fiber surface of the fiber (shaded part in the figure) has gradient surface energy characteristics (hydrophilic polyvinyl pyrrolidone K-90 (PVPK-90) / poloxamer 407 (P407) is grafted by ultraviolet light, and the wettability of the upper part is better than that of the lower part by changing the proportion of P407). Under the combined influence, the contact angle of the upper part of the liquid-conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light is measured to be 20°, the contact angle of the lower part of the liquid-conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light is measured to be 39°, and the contact angle of the sweat in the area where PVPK-90 / P407 is not grafted by ultraviolet light is measured to be greater than 130°.
[0159] The liquid collection layer 13 is made of a uniform-scale TPU composite nanofiber membrane, and the local area of the uniform-scale TPU composite nanofiber membrane (such as Figure 1 The shaded part in the figure) is grafted with hydrophilic PVPK-90 / P407 by ultraviolet light, and the wettability of the hydrophilic treated area to sweat is uniform and better than that of the upper part of the liquid-conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light. The contact angle is measured to be 15°, and the contact angle of the area where PVPK-90 / P407 is not grafted by ultraviolet light is measured to be greater than 133°.
[0160] The volatile layer 14 is made of a uniform-sized TPU composite nanofiber membrane, the entire area of which is grafted with hydrophilic PVPK-90 / P407 by ultraviolet light, and the wettability to sweat after hydrophilic treatment is worse than that of the liquid collection layer 13, but better than the upper part of the liquid conducting layer 12 where PVPK-90 / P407 is grafted by ultraviolet light, and the contact angle is measured to be 18°.
[0161] The sensing electrode 21, in this embodiment, adopts a three-electrode system for sweat uric acid detection, including a counter electrode, a reference electrode and a working electrode. The reference electrode is Ag / AgCl, the counter electrode is a cured carbon conductive ink, and the working electrode is a carbon conductive ink modified with a uric acid detection solution.
[0162] The signal transmission electrode 22 is made of a liquid metal pattern, the mass ratio of gallium:indium:tin is 0.68:0.215:0.1, and the melting point is 11°C.
[0163] The electrode deposition layer 23 is made of a graphene oxide (GO) / TPU composite nanofiber membrane with a patterned structure and uniform scale. It wets the liquid metal and the contact angle is measured to be 26°. Other nanofiber membranes of the present invention do not wet the liquid metal and the contact angle is measured to be greater than 136°.
[0164] like Figure 2 As shown, the preparation method of the in-situ detection sensor for body surface sweat comprises the following steps:
[0165] S1. Preparation of electrode deposition layer 23: 0.01 g GO powder solution was dissolved in 2 g dimethylacetamide (DMAC) solvent by ultrasound, and then 0.9 g TPU particles were added, and finally magnetic stirring was performed for 3 hours to obtain GO / TPU composite precursor solution; the prepared GO / TPU composite precursor solution was loaded into a syringe, and a patterned GO / TPU composite nanofiber membrane was prepared on the surface of a silicon wafer by an electrostatic direct writing process (2 kV direct writing voltage, 150 uL / h liquid supply rate, 1.5 cm direct writing distance), thereby preparing the electrode deposition layer 23. The pattern of the electrode deposition layer 23 can be obtained by the desired pattern from the direct writing substrate motion path.
[0166] S2. Preparation of sensing electrode 21: first, Ag / AgCl ink is screen-printed and dried to obtain Ag / AgCl reference electrode; the counter electrode is prepared by screen-printing carbon conductive ink; the working electrode is first prepared by screen-printing carbon conductive ink, and 60uL of uric acid detection solution is dripped on the working electrode area by a pipette, and then dried at room temperature and repeated the above operation 5 times to allow the uric acid detection solution to completely adhere to the surface of the working electrode. Among them, the preparation method of the uric acid detection solution is: first dissolve 0.0841g of 3-methyl-1H-1,2,4-triazole in 2 mL of deionized water, dissolve 0.0594g of Zn(NO3)2·6H2O and 15mg of uricase in 2 mL of deionized water, and then stir the two solutions obtained above at room temperature for 24 hours, collect the white precipitate after centrifugation; take 2mg of the above precipitate and dissolve it in deionized water by ultrasonication for 15 minutes, then take 50uL of the above dispersion and 10uL of Nafion solution, mix them evenly to obtain the uric acid detection solution.
[0167] S3, preparation of liquid collection layer 13: 0.9 g of TPU particles were dissolved in 2 g of DMAC solvent by magnetic stirring for 3 h, and the obtained TPU precursor solution was loaded into a syringe; PVPK-90, P407 and photoinitiator 6967 were fully dissolved by a constant temperature (80 ° C) magnetic stirrer, and the mass ratio of PVPK-90, P407 and photoinitiator 6967 was 1:4:3; then pure TPU nanofibers were prepared by electrostatic spinning of TPU precursor, and PVPK-90 / P407 solution was sprayed on the surface of the pure TPU nanofibers prepared above by electrostatic spraying process during spinning; finally, the mixture was irradiated for 4 min through a mask and ultraviolet light (wavelength of 568.7 nm), and hydrophilic TPU nanofibers were obtained in the irradiated area after curing, and the other parts were not wetted by sweat because they were not treated with ultraviolet light. During the spinning process, the electrospinning voltage was 20 kV, the liquid supply rate was 300 uL / h, and the spinning spacing was 15 cm, so that multi-scale TPU nanofibers with uniform fiber diameter could be obtained; while electrospinning TPU nanofibers, PVPK-90 / P407 solution was electrostatically sprayed, with a spray voltage of 20 kV, a liquid supply rate of 200 uL / h, and a spray spacing of 15 cm.
[0168] S4, preparation of volatile layer 14: electrospinning and depositing pure TPU nanofibers on the above-mentioned liquid collection layer 13, and at the same time electrostatically spraying PVPK-90 / P407 solution, wherein the mass ratio of PVPK-90:P407 is 1:3; then irradiating the entire fiber membrane with ultraviolet light (wavelength of 568.7 nm) for 4 minutes, and hydrophilic TPU nanofibers can be obtained after curing; the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, the spinning spacing is 15 cm, the spray voltage is 20 kV, the liquid supply rate is 200 uL / h, and the spray spacing is 15 cm.
[0169] S5. Preparation of the signal transmission electrode 22: The electrode deposition layer 23, the sensing electrode 21, the liquid collection layer 13 and the volatile layer 14 prepared on the silicon wafer are removed from the silicon wafer, and then the liquid metal alloy is adhered to the electrode deposition layer 23 by a transfer method. Since the electrode deposition layer 23 wets the liquid metal (the contact angle is measured to be 26°), and the sensing electrode 21 does not wet the liquid metal (the contact angle is measured to be 136°), the liquid metal will automatically adhere to the electrode deposition layer 23. The reason why the liquid metal adheres to the GO / TPU composite nanofiber membrane is that GO is rich in -OH functional groups and adheres to the liquid metal Ga2O3 oxide layer through hydrogen bonds.
[0170] S6, preparation of liquid-conducting layer 12: peel off the composite film prepared above from the silicon wafer, and then electrospin deposit multi-scale TPU composite nanofibers on the peeled surface, and electrostatically spray PVPK-90 / P407 solution at the same time, and finally irradiate for 4 minutes through a mask and ultraviolet light (wavelength of 568.7 nm). After curing, hydrophilic TPU nanofibers can be obtained in the irradiated area, and other parts are not wetted by sweat because they are not treated with ultraviolet light. In the spinning process, the electrospinning voltage is 20 kV, the liquid supply rate is 300 uL / h, and the spinning spacing is 15 cm; then every 15 minutes, the electrospinning voltage is reduced by 3 kV, so that multi-scale fibers with gradually increasing fiber diameters from bottom to top can be obtained; at the same time, every 15 minutes, the liquid supply rate is increased by 15 uL / h, the higher the rate, the faster the spinning jet is ejected, and the denser the fiber deposition is, so that multi-scale fibers with gradually decreasing pore structures from bottom to top can be obtained. While electrospinning TPU nanofibers, PVPK-90 / P407 solution was electrostatically sprayed. The initial mass ratio of PVPK-90:P407:photoinitiator 6967 was 1:4:3. Thereafter, every 15 min, the mass ratio of photoinitiator 6967 remained unchanged, and the mass ratio of PVPK-90:P407 decreased in sequence of 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, etc. The spray voltage was 20 kV, the liquid supply rate was 200 uL / h, and the spray spacing was 15 cm.
[0171] S7. Preparation of the hydrophobic layer 11: The multi-scale TPU composite nanofibers were deposited on the liquid conductive layer 12 prepared above by electrospinning. During the spinning process, the electrospinning voltage was 20 kV, the liquid supply rate was 300 uL / h, and the spinning spacing was 15 cm. Because the hydrophobic layer 11 was not grafted with PVPK-90 / P407 by ultraviolet light, it was not wetted by sweat.
[0172] Under the action of the secretion pressure of the sweat glands of the skin, the gradient capillary force of the hydrophobic layer 11 and the hydrophilic capillary force of the liquid conducting layer 12, the sweat will be self-driven by the hydrophobic layer 11 to penetrate into the liquid conducting layer 12. Because the hydrophobic layer 11 does not wet sweat, no sweat will remain on the contact surface with the skin, maintaining long-term wearing comfort; the liquid conducting layer 12 has a gradient fiber diameter and gradient surface energy. Under the action of Laplace pressure, the sweat will be self-driven to penetrate from the lower part of the liquid conducting layer 12 to the upper part of the liquid conducting layer 12, and then stay in the liquid collection layer 13 and fully contact with the detection electrode 2. The volatile layer 14 has a large volatile area, which ensures that the sweat after detection will evaporate in time to avoid cross-contamination between new and old sweat; on the other hand, in the sweat wetting area, the sweat contact angle of the volatile layer 14 is 18°, the contact angle of the liquid collecting layer 13 is 15°, and the upper contact angle of the liquid conducting layer 12 is 20° and the lower contact angle is 39°; the wettability of the liquid collecting layer 13 is better than that of the volatile layer 14, and the sweat will stay in the liquid collecting layer 13 to ensure that the sweat can fully contact the detection electrode 2; the wettability of the volatile layer 14 is better than that of the liquid conducting layer 12, which ensures that the detected sweat will not flow back and prevent cross-contamination between new and old sweat. The in-situ detection sensor for body surface sweat based on composite nanofibers provided in this embodiment has an overall porous structure with good air permeability, which avoids inflammation caused by long-term wear. In addition, the signal transmission electrode adopts liquid metal, which can ensure the stability of signal transmission under deformation interference. When sweat penetrates into the liquid collection layer 13, it will contact the sensing electrode 21. The sweat will cause the change of current under the action of urate oxidase modified by the working electrode.
[0173] In order to verify the feasibility and deformation resistance of the sensor, the current response of the sensor to different glucose concentrations in the initial state and the 30% stretched state was investigated. Figure 5 As shown, under the condition of constant voltage of -0.1V, the current change of the sensing electrode 21 shows a linear increasing relationship with the glucose concentration. When the glucose concentration increases from 0.05 mmol / L to 2.5 mmol / L, the current response increases from 0.27 uA to 3.48 uA. It can also be found that stretching has little effect on the current response. Under a 30% stretching state, when the glucose concentration increases from 0.05 mmol / L to 2.5 mmol / L, the current response increases from 0.36 uA to 3.41 uA, indicating that the liquid metal electrode has good signal transmission stability and can resist the influence of skin deformation on the sensing performance.
[0174] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A sensor for in-situ detection of sweat on the body surface based on composite nanofibers, characterized in that: It comprises a flexible substrate (1) and a detection electrode (2); Wherein, the flexible substrate (1) comprises: Hydrophobic layer (11); A liquid-conducting layer (12) disposed on the hydrophobic layer (11), the liquid-conducting layer (12) comprising a sweat non-wetting area and a first sweat wetting area (121), the contact angle of the first sweat wetting area (121) gradually decreasing from close to the hydrophobic layer (11) to away from the hydrophobic layer (11), and the contact angle of the first sweat wetting area (121) on the side close to the hydrophobic layer (11) is smaller than the contact angle of the hydrophobic layer (11); a liquid collection layer (13) disposed on the liquid conducting layer (12), the liquid collection layer (13) comprising a sweat non-wetting area and a second sweat wetting area (131), the contact angle of the second sweat wetting area (131) being smaller than the contact angle of the first sweat wetting area (121) on a side away from the hydrophobic layer (11); A volatile layer (14) is disposed on the liquid collection layer (13), wherein the volatile layer (14) has a third sweat wetting area (141), wherein the contact angle of the third sweat wetting area (141) is greater than the contact angle of the second sweat wetting area (131) and is less than the contact angle of the first sweat wetting area (121) on a side away from the hydrophobic layer (11); The detection electrode (2) is arranged in the liquid collection layer (13) and is in contact with the second sweat wetting area (131).
2. The body surface sweat in-situ detection sensor according to claim 1, characterized in that: The liquid conducting layer (12), the liquid collecting layer (13) and the volatilization layer (14) are all nanofiber membranes; The surface energy of the nanofiber membrane in the first sweat wetting area (121) gradually increases from a direction close to the hydrophobic layer (11) to a direction away from the hydrophobic layer (11), the fiber diameter of the nanofiber membrane in the first sweat wetting area (121) gradually increases from a direction close to the hydrophobic layer (11) to a direction away from the hydrophobic layer (11), and the size of the gaps between the fibers gradually decreases from a direction close to the hydrophobic layer (11) to a direction away from the hydrophobic layer (11); The surface energy of the nanofiber membrane in the second sweat wetting area (131) is smaller than the surface energy of the nanofiber membrane on the side of the first sweat wetting area (121) away from the hydrophobic layer (11); The surface energy of the nanofiber membrane in the third sweat wetting area (141) is greater than the surface energy of the nanofiber membrane in the second sweat wetting area (131), and is less than the surface energy of the nanofiber membrane on the side of the first sweat wetting area (121) away from the hydrophobic layer (11).
3. The body surface sweat in-situ detection sensor according to claim 1, characterized in that: The detection electrode (2) comprises: an electrode deposition layer (23) disposed on a side of the liquid collection layer (13) close to the liquid conducting layer (12), one end of the electrode deposition layer (23) being in contact with the second sweat wetting area (131); a sensing electrode (21), disposed on the electrode deposition layer (23) and in contact with the second sweat wetting area (131); A signal transmission electrode (22) disposed at one end of the electrode deposition layer (23) away from the second sweat wetting area (131); Wherein, the contact angle of the electrode deposition layer (23) is smaller than the contact angle of the sensing electrode (21).
4. The body surface sweat in-situ detection sensor according to claim 3, characterized in that: The contact angle of the hydrophobic layer (11) to sweat is 140-150°; The contact angle of the first sweat wetting area (121) on the side close to the hydrophobic layer (11) to sweat is 40-50°, and the contact angle of the first sweat wetting area (121) on the side away from the hydrophobic layer (11) to sweat is 20-30°; The contact angle of the second sweat wetting area (131) to sweat is 14-16°; The contact angle of the third sweat wetting area (141) to sweat is 17-19°; The contact angle of the electrode deposition layer to the liquid metal is 20-30°; The area of the third sweat wetting area (141) is greater than the area of the second sweat wetting area (131).
5. A method for preparing a sensor for in-situ detection of sweat on the body surface based on composite nanofibers according to any one of claims 1 to 4, characterized in that: The following steps are involved: preparing an electrode deposition layer (23); Preparing a sensing electrode (21) on the electrode deposition layer (23); Depositing a nanofiber membrane with a uniform structure on the sensing electrode (21), modifying the wettability of a local area of the nanofiber membrane to form a second sweat wetting area (131), and obtaining a liquid collection layer (13); Depositing a nanofiber membrane with a uniform structure on the liquid collection layer (13), modifying the wettability of a local area or the entire area of the nanofiber membrane to form a third sweat wetting area (141), and obtaining a volatile layer (14); The electrode deposition layer (23), the sensing electrode (21), the liquid collection layer (13) and the volatile layer (14) are removed, and a signal transmission electrode (22) is prepared on the electrode deposition layer (23); A nanofiber membrane is deposited on a side of the liquid collection layer (13) away from the volatile layer (14), the diameter and pore size of the nanofibers are regulated by an electrospinning process, and the wettability of a local area of the nanofiber membrane is modified by combining a mask plate and laser modification to form a first sweat wetting area (121), thereby obtaining a liquid conducting layer (12); A nanofiber membrane is deposited on a side of the liquid-conducting layer (12) away from the liquid-collecting layer (13) to obtain a hydrophobic layer (11).
6. The preparation method according to claim 5, characterized in that: The preparation method specifically comprises: The electrode deposition layer was prepared by forming a graphene oxide / TPU composite nanofiber film on a silicon wafer by an electrostatic direct writing process (23); Preparing a sensing electrode (21) on the electrode deposition layer (23) by a screen printing process, wherein the sensing electrode (21) comprises a counter electrode, a reference electrode and a working electrode; Depositing a nanofiber membrane with a uniform structure on the sensing electrode (21) by an electrospinning process, and modifying the wettability of a local area of the nanofiber membrane by combining a mask and laser modification to form a second sweat wetting area (131), thereby obtaining a liquid collection layer (13); Depositing a nanofiber membrane with a uniform structure on the prepared liquid collection layer (13) by an electrospinning process, and modifying the wettability of a local area or the entire area of the nanofiber membrane by combining a mask plate and laser modification to form a third sweat wetting area (141), thereby obtaining a volatile layer (14); The electrode deposition layer (23), the sensing electrode (21), the liquid collection layer (13) and the volatile layer (14) are removed from the silicon wafer, and a liquid metal alloy is formed on the electrode deposition layer (23) by a transfer process to obtain a signal transmission electrode (22); A nanofiber membrane is deposited on a side of the liquid collection layer (13) away from the volatile layer (14), the diameter and pores of the nanofibers are regulated by an electrostatic spinning process, and the wettability of a local area of the nanofiber membrane is modified by combining a mask plate and laser modification to form a first sweat wetting area (121), thereby obtaining a liquid conducting layer (12); wherein the surface energy gradient of the nanofiber membrane is obtained by controlling the laser treatment time, and the diameter and pores of the nanofibers are regulated by the applied spinning voltage, the spinning deposition spacing and the liquid supply rate; A nanofiber membrane is deposited on a side of the liquid-conducting layer (12) away from the liquid-collecting layer (13), and the diameter and pore size of the nanofibers are regulated by an electrostatic spinning process to obtain a hydrophobic layer (11).
7. The preparation method according to claim 5, characterized in that: The steps of preparing the electrode deposition layer (23) specifically include: The graphene oxide powder solution is dispersed in a solvent, and TPU particles are added to mix to obtain a GO / TPU composite precursor solution; the prepared GO / TPU composite precursor solution is used to prepare a GO / TPU composite nanofiber membrane on a silicon wafer surface by an electrostatic direct writing process to prepare an electrode deposition layer (23); The step of preparing the sensing electrode (21) on the electrode deposition layer (23) specifically comprises: An Ag / AgCl reference electrode is prepared by screen printing Ag / AgCl ink and drying; a counter electrode is prepared by screen printing carbon conductive ink; a working electrode is prepared by screen printing carbon conductive ink, and a glucose oxidase solution is dripped into the working electrode area to make the glucose oxidase adhere to the surface of the working electrode to obtain a sensing electrode (21); The step of obtaining the liquid collection layer (13) specifically comprises: Dissolving TPU particles in a solvent to obtain a TPU precursor solution; dissolving PVPK-90, P407 and a photoinitiator to obtain a PVPK-90 / P407 solution; preparing the TPU precursor solution into pure TPU nanofibers by electrostatic spinning, and spraying the PVPK-90 / P407 solution on a local area of the surface of the pure TPU nanofibers by an electrostatic spraying process; forming a second sweat wetting area (131) by masking and ultraviolet irradiation, and forming a sweat non-wetting area in an area not irradiated with ultraviolet light, thereby obtaining a liquid collection layer (13); The step of obtaining the volatile layer (14) specifically includes: Dissolving TPU particles in a solvent to obtain a TPU precursor solution; dissolving PVPK-90, P407 and a photoinitiator to obtain a PVPK-90 / P407 solution; preparing the TPU precursor solution into pure TPU nanofibers by electrostatic spinning, and spraying the PVPK-90 / P407 solution on a local area or the entire area of the surface of the pure TPU nanofibers by an electrostatic spraying process; forming a third sweat wetting area (141) by masking and irradiating with ultraviolet light to obtain a volatile layer (14); The step of obtaining the signal transmission electrode (22) specifically includes: The electrode deposition layer (23), the sensing electrode (21), the liquid collection layer (13) and the volatile layer (14) are removed from the silicon wafer, and a liquid metal alloy is formed on the electrode deposition layer (23) by a transfer process to obtain a signal transmission electrode (22); wherein the liquid metal alloy is a gallium-indium-tin liquid alloy; The steps of obtaining the liquid conducting layer (12) specifically include: Dissolving TPU particles in a solvent to obtain a TPU precursor solution; dissolving PVPK-90, P407 and a photoinitiator to obtain a PVPK-90 / P407 solution; reducing the electrospinning voltage by an electrospinning interval to make the TPU precursor solution into pure TPU nanofibers; spraying the PVPK-90 / P407 solution on a local area of the surface of the pure TPU nanofibers by an electrostatic spraying process interval, wherein the mass ratio of PVPK-90 to P407 in the PVPK-90 / P407 solution gradually increases; forming a first sweat wetting area (121) by a mask and ultraviolet light irradiation, and forming a sweat non-wetting area in an area not irradiated with ultraviolet light to obtain a liquid conductive layer (12); The steps of obtaining the hydrophobic layer (11) specifically include: The TPU particles are dissolved in a solvent to obtain a TPU precursor solution; the TPU precursor solution is made into pure TPU nanofibers by electrospinning to obtain a hydrophobic layer (11).
8. The preparation method according to claim 7, characterized in that: In the step of preparing the electrode deposition layer (23), the mass ratio of the graphene oxide powder solution, the solvent and the TPU particles is 0.008-0.012:1.8-2.2:0.8-1, and the electrostatic direct writing process parameters include: the direct writing voltage is 1.8-2.2 kV, the liquid supply rate is 145-155 uL / h, and the direct writing distance is 1.4-1.6 cm; In the step of obtaining the liquid collection layer (13), the mass ratio of the solvent to the TPU particles is 1.8-2.2:0.8-1, the mass ratio of PVPK-90 to P407 is 1:3.8-1:4.2, the electrospinning voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, the spinning spacing is 14-16 cm, the spray voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, and the spray spacing is 14-16 cm; In the step of obtaining the volatile layer (14), the mass ratio of the solvent to the TPU particles is 1.8-2.2:0.8-1, the mass ratio of PVPK-90 to P407 is 1:2.8-1:3.2, the electrospinning voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, the spinning spacing is 14-16 cm, the spray voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, and the spray spacing is 14-16 cm; In the step of obtaining the signal transmission electrode (22), the mass ratio of gallium:indium:tin is 0.68:0.215:0.1; In the step of obtaining the hydrophobic layer (11), the mass ratio of the solvent to the TPU particles is 1.8-2.2:0.8-1, the electrospinning voltage is 18-22 kV, the liquid supply rate is 280-320 uL / h, and the spinning spacing is 14-16 cm.
9. The preparation method according to claim 7, characterized in that: In the step of obtaining the liquid conducting layer (12), The initial electrospinning voltage was 18-22 kV, and the electrospinning voltage was reduced by 2.5-3.5 kV every 10-25 min. The liquid supply rate was 280-320 uL / h, and the spinning spacing was 14-16 cm. Each interval was 14-16 min, the mass ratio of PVPK-90 and P407 in the PVPK-90 / P407 solution gradually increased from 1:3.8-1:4.2 to 2.8:1-3.2:1, the spray voltage was 18-22 kV, the liquid supply rate was 180-220 uL / h, and the spray spacing was 14-16 cm.
10. The preparation method according to claim 9, characterized in that: The mass ratios of PVPK-90 and P407 in the PVPK-90 / P407 solution are 1:4, 1:3, 1:2, 1:1, 2:1, and 3:1, respectively.
Citation Information
Patent Citations
Novel fiber type sweat ion detection sensor and preparation method thereof
CN114295698A
One-way permeable sweat sensor, manufacturing method thereof and wearable device
CN114680883A
Sweat sensor and preparation method thereof
CN110823968A
Multi-channel fiber-based sweat collection system, sweat sensing system and preparation method thereof
CN111759359A
Cited By
Flexible wearable sweat bio-component real-time monitoring bracelet and its detection method
CN122556981A
Integrated high-sensitivity high-stability sweat monitoring sensing yarn and preparation method thereof
CN122687384A